Taxonomy and secondary metabolites of selected actinomycete strains and monascus kaoliang KB 20 M 10.2 - Suchada Jongrungruangchok (Chulalongkorn University, 2014)
Thesis (Ph.D.)--Chulalongkorn University, 2004